Non-aqueous battery electrolyte and battery
By using a non-aqueous electrolyte containing fluorovinyl carbonate, 1,3-propane sulfonate and B-O structure compounds in lithium-ion batteries, a stable SEI and CEI film was formed, and the volume changes of silicon negative electrode materials were solved. Battery performance issues significantly improve cycle performance and high-temperature storage performance.
Patent Information
- Application Number
- CN202411257327.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The volume of the silicon negative electrode material in lithium-ion batteries varies greatly during the charging and discharging process, resulting in electrical isolation, solid electrolyte interface rupture and high-resistance negative/electrolyte interface layer, affecting the cycling performance and high-temperature storage performance.
A non-aqueous battery electrolyte solution is used, including electrolyte salts, organic solvents, fluorovinyl carbonate, 1,3-propane sulfonate lactone and vinyl sulfate as the first additive, and contains B-O structure and carbon-carbon triple bonds As the second additive, the compound forms a uniform and dense SEI film and CEI film, which synergizes with the negative electrode and positive electrode surface of the battery to improve interface stability and chemical stability.
It effectively limits the volume expansion of the negative electrode material, improves the cycling performance and high-temperature storage performance of the battery, reduces interface side reactions and irreversible phase change, improves the structural stability of the electrode interface, and is low in cost and easy to achieve.
Smart Images

Figure BDA0005034478860000021 
Figure BDA0005034478860000022 
Figure BDA0005034478860000031
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary batteries and relates to a non-aqueous electrolyte and a battery. Background Art
[0002] The rapidly growing electric vehicle (EV) market has driven the development of lithium-ion batteries (LIBs) with higher energy density and longer cycle life. High-nickel layered oxide materials have higher specific capacity, and silicon / graphite composite negative electrode materials have high capacity characteristics and can improve cycle performance. The pairing of high-nickel layered oxide positive electrode materials and silicon / graphite composite negative electrode materials is conducive to improving the energy density of lithium-ion batteries at a lower cost.
[0003] However, the volume change of silicon negative electrode is large during the charge and discharge process, and the maximum volume change is even more than 300%. Although the combination of silicon and graphite can alleviate the volume change, the volume expansion rate of silicon is still high. Repeated volume expansion-contraction leads to the crushing of Si particles, which will lead to electrical isolation; it will also lead to the rupture, continuous formation and subsequent impedance growth of the solid electrolyte interface (SEI) film; and consume the electrolyte on the newly exposed Si surface, resulting in the active Li + Worse still, transition metal (TM) ions dissolve from the cathode material and then deposit on the anode surface, which catalyzes electrolyte decomposition and leads to a high-resistance anode / electrolyte interface layer, resulting in poor battery cycling performance and high-temperature storage, showing a more serious adverse effect on battery performance. Summary of the invention
[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a non-aqueous battery electrolyte and a battery with excellent cycle performance and high-temperature storage performance.
[0005] One of the objects of the present invention is to provide a non-aqueous battery electrolyte, the electrolyte comprising an electrolyte salt, an organic solvent, a first additive and a second additive;
[0006] The first additive includes fluoroethylene carbonate, 1,3-propane sultone and vinyl sulfate;
[0007] The second additive includes one or more of compound A as shown in formula I, compound B as shown in formula II, or compound C as shown in formula III;
[0008]
[0009] wherein R1, R4, and R5 are each independently hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, C3-C6 cycloalkyl, substituted or unsubstituted phenyl, nitrogen-containing phenyl substituent, furyl, thienyl, pyrrolyl, or pyridyl;
[0010] R2 and R3 are each independently a C1-C6 alkyl group.
[0011] Preferably, the substituent of the C1-C6 alkyl group includes halogen, benzene or a hydrocarbonoxy group, and the hydrocarbonoxy group includes an alkoxy group, an alkenyloxy group or an alkynyloxy group.
[0012] Preferably, the substituent of the C2-C6 alkenyl group includes halogen or benzene.
[0013] Preferably, the substituent of the C2-C6 alkynyl group includes halogen or benzene.
[0014] Preferably, the substituents of the phenyl group include halogen, alkyl or halogen-substituted alkyl.
[0015] Preferably, the nitrogen-containing benzene substituent includes phenylnitro, phenylamino or benzonitrile.
[0016] Preferably, R1 is -C(CH3)3, -C6H4C(CH3)3, -CH3 or CH2CHCH2OCH2-.
[0017] Preferably, R4 is -CH2CH2CH3, -CH2OCH3, CF3, -C6H4CF3, -C6H 11 Or -C6H5.
[0018] Preferably, R5 is -H, -CH2OCH2CCH, -C6H5 or -C5H4N.
[0019] Preferably, compound A comprises one or more of the following compounds:
[0020]
[0021]
[0022] Preferably, compound B comprises one or more of the following compounds:
[0023]
[0024] Preferably, compound C comprises one or more of the following compounds:
[0025]
[0026]
[0027] Preferably, based on 100% of the total mass of the electrolyte, the mass percentage of the second additive is 0.5-4%.
[0028] Preferably, the mass percentage of the first additive is 3-10%.
[0029] Preferably, in the first additive, the mass ratio of fluoroethylene carbonate, 1,3-propane sultone and vinyl sulfate is 5:2:1.5.
[0030] Preferably, the electrolyte salt includes one or a combination of XPF6, XClO4, XBF4, XAsF6, XFSI, XTFSI, XBOB, XODFB, XCF3SO3, XPO2F2 or XOTFB.
[0031] Wherein, X includes any one of Li, Na or K.
[0032] Preferably, in the lithium ion battery, X is Li.
[0033] Preferably, the total mass of the electrolyte is 100%, and the mass percentage of the electrolyte salt is 6.25% to 37.5%;
[0034] Preferably, the lithium salt comprises lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the mass ratio of lithium hexafluorophosphate to lithium bis(fluorosulfonyl)imide is 7.5:9.
[0035] Preferably, the organic solvent comprises one or more of carbonates, halogenated carbonates, carboxylates, propionates, fluoroethers, aromatic hydrocarbons or halogenated aromatic hydrocarbons.
[0036] Preferably, the organic solvent includes ethylene carbonate, ethyl methyl carbonate and diethyl carbonate.
[0037] Preferably, the mass ratio of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate is 25:70:5.
[0038] Preferably, based on the total mass of the electrolyte being 100%, the mass percentage of the organic solvent is 40% to 85%, preferably 73%.
[0039] A second object of the present invention is to provide a battery, wherein the battery comprises the non-aqueous battery electrolyte as described above.
[0040] Preferably, the battery comprises a lithium ion battery, a sodium ion battery, a potassium ion battery or a supercapacitor.
[0041] Preferably, the negative electrode material of the lithium-ion battery is graphite, a composite material of single crystal silicon and graphite, or a composite material of silicon oxide and graphite, lithium titanate or Nb2O5.
[0042] The beneficial effects of the present invention include:
[0043] In the present invention, fluoroethylene carbonate, 1,3-propane sultone and vinyl sulfate are used as the first additive, and one or more of compound A, compound B or compound C containing BO structure and carbon-carbon triple bond are used as the second additive. The first additive and the second additive cooperate with each other to form a SEI film of organic polymer and inorganic compound on the negative electrode surface of the battery. The structure of the SEI film is uniform and dense, and has high chemical stability, and has a certain hardness and elasticity. When the volume of the negative electrode fluctuates, the SEI can remain intact to avoid damage, thereby further limiting the growth of the SEI film, which is beneficial to improving the long cycle performance of the battery. At the same time, the first additive and the second additive cooperate with each other to form a dense CEI film of organic polymer and inorganic structure covalently bonded on the positive electrode surface of the battery, which can avoid the penetration of electrolyte, reduce interface side reactions, and reduce irreversible phase changes, which is beneficial to improving the high temperature storage performance of the battery. At the same time, the use of multiple elements as additives can enrich the interface film components of the electrode / electrolyte, thereby improving the structural stability of the interface film, and has the advantages of small addition amount, low cost and simple synthesis, easy to implement, and conducive to wide promotion and application. The electrolyte of the present invention is particularly suitable for lithium ion batteries whose negative electrode materials are graphite, composite materials of single crystal silicon and graphite, or composite materials of silicon dioxide and graphite, and can limit the volume expansion of the negative electrode material and improve the cycle performance of the battery. DETAILED DESCRIPTION
[0044] In the following description, certain specific details are included to provide a comprehensive understanding of each disclosed embodiment. However, one skilled in the relevant art will recognize that the embodiments can be implemented without one or more of these specific details, but with other methods, components, materials, etc.
[0045] Unless otherwise required herein, the words "include" and "comprising" should be interpreted as having an open and inclusive meaning, ie, "including but not limited to".
[0046] References to "one embodiment" or "an embodiment" or "a preferred embodiment" or "certain embodiments" throughout this specification mean that the specific referenced elements, structures or features described in connection with the embodiment are included in at least one embodiment. Therefore, the phrases "in one embodiment" or "in an embodiment" or "in a preferred embodiment" or "in certain embodiments" appearing in different places throughout the specification do not necessarily all refer to the same embodiment. In addition, the specific elements, structures or features may be combined in any appropriate manner in one or more embodiments.
[0047] According to a first aspect of the present invention, there is provided a non-aqueous battery electrolyte, the electrolyte comprising an electrolyte salt, an organic solvent, a first additive and a second additive;
[0048] The first additive includes fluoroethylene carbonate, 1,3-propane sultone and vinyl sulfate;
[0049] The second additive includes one or more of compound A as shown in formula I, compound B as shown in formula II, or compound C as shown in formula III;
[0050]
[0051] wherein R1, R4, and R5 are each independently hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, C3-C6 cycloalkyl, substituted or unsubstituted phenyl, nitrogen-containing phenyl substituent, furyl, thienyl, pyrrolyl, or pyridyl;
[0052] R2 and R3 are each independently a C1-C6 alkyl group.
[0053] In the present invention, on the negative electrode surface of the battery, the carbon-carbon triple bond in the second additive is conducive to the formation of a flexible organic polymer film on the negative electrode, and the -BO- bond will also construct a cross-linked structure inside the film, which can effectively improve the stability of the SEI film. And the BO bond is evenly distributed in the organic polymer film, which is conducive to the coordinated construction of a uniform, dense SEI film with high chemical stability and hardness with fluoroethylene carbonate, 1,3-propane sultone and vinyl sulfate, and improves long-cycle performance. The combined use of the two can enhance the modulus and uniformity of the SEI and form an elastic SEI film. The SEI film should have a flexible and adaptable structure, and be supplemented with appropriate mechanical strength to adapt to the volume change of the negative electrode. It maintains its integrity during the volume fluctuation of the negative electrode, further limiting the growth of the SEI film.
[0054] At the same time, on the positive electrode surface of the battery, the first additive and the second additive work together to form a dense CEI film in which the organic polymer and the inorganic structure are covalently bonded, which can prevent the penetration of electrolytes, reduce interfacial side reactions, and alleviate irreversible phase changes, which is beneficial to improving the high-temperature storage performance of the battery.
[0055] The present invention can effectively improve the performance of the whole battery by constructing a chemically and mechanically stable interface phase on both sides of the electrode.
[0056] At the same time, the borate produced by the decomposition of the B-containing additive can effectively capture F- and reduce the impedance of the organic polymer film formed by the unsaturated bonds in the interface of the present invention, so that the lithium ion migration rate is faster and the migration number is higher, so that the concentration polarization generated during the ion consumption process on the electrode surface is smaller, which is conducive to maintaining the stability of the electrode interface. At the same time, elements such as boron and oxygen can enrich the interface film components of the electrode / electrolyte, which is also conducive to improving the structural stability of the interface film.
[0057] The electrolyte of the present invention is particularly suitable for lithium-ion batteries whose negative electrode materials are graphite, a composite material of single crystal silicon and graphite, or a composite material of silicon oxide and graphite, and can limit the volume expansion of the negative electrode material and improve the cycle performance of the battery.
[0058] In a preferred embodiment of the present invention, in R1, R4 and R5, the substituent of the C1-C6 alkyl group includes halogen, benzene or hydrocarbonoxy, and the hydrocarbonoxy includes alkoxy, alkenyloxy or alkynyloxy.
[0059] Preferably, the substituents of the C2-C6 alkenyl group include halogen or benzene, preferably fluorine or benzene.
[0060] Preferably, the substituent of the C2-C6 alkynyl group includes halogen or benzene.
[0061] Preferably, the substituents of the phenyl group include halogen, alkyl or halogen-substituted alkyl.
[0062] Preferably, the nitrogen-containing benzene substituent includes phenylnitro, phenylamino or benzonitrile.
[0063] Preferably, R2 and R3 are each independently a C1-C3 alkyl group, which is beneficial to reducing the viscosity of the electrolyte and thus improving the conductivity.
[0064] In a preferred embodiment of the present invention, R1 is -C(CH3)3, -C6H4C(CH3)3, -CH3 or CH2CHCH2OCH2-.
[0065] Preferably, R4 is -CH2CH2CH3, -CH2OCH3, CF3, -C6H4CF3, -C6H 11 Or -C6H5.
[0066] Preferably, R5 is -H, -CH2OCH2CCH, -C6H5 or -C5H4N.
[0067] In a preferred embodiment of the present invention, compound A comprises one or more of the following compounds;
[0068]
[0069] In a preferred embodiment of the present invention, compound B comprises one or more of the following compounds:
[0070]
[0071] In a preferred embodiment of the present invention, compound C comprises one or more of the following compounds;
[0072]
[0073] Preferably, the first additive includes compound C as shown in formula III-4.
[0074] In the present invention, compound C shown in formula III-4 contains a nitrogen-containing pyridine group, which is beneficial to the formation of a stable interface film containing LixNOy on the surface of the positive and negative electrodes, and cooperates with the carbon-carbon triple bond and the borate group, which is more beneficial to inhibiting the side reaction between the electrolyte and the positive electrode interface under high voltage, and at the same time inhibiting the dissolution of transition metal ions and the damage of the transition metal ions to the negative electrode interface film, thereby improving the efficiency and cycle performance of the battery, especially improving the electrochemical performance of the battery at high temperature, and has the advantages of small addition amount, low cost and simple synthesis, easy to realize, and conducive to wide promotion and application.
[0075] In a preferred embodiment of the present invention, based on the total mass of the electrolyte being 100%, the mass percentage of the second additive is 0.5-4%, preferably 2%.
[0076] Preferably, the mass percentage of the first additive is 3-10%, preferably 8.5%.
[0077] In the present invention, 3-10% of the first additive and 0.5-4% of the second additive cooperate with each other. It is more conducive to the formation of SEI films and CEI films with uniform structure and stable performance. The mass percentage of the first additive is, for example, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%; or any point value between the above two. The mass percentage of the second additive is, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5% or 4%, or any point value between the above two.
[0078] In a preferred embodiment of the present invention, in the first additive, the mass ratio of fluoroethylene carbonate, 1,3-propane sultone and vinyl sulfate is 5:2:1.5.
[0079] In the present invention, fluoroethylene carbonate, 1,3-propane sultone and vinyl sulfate in a mass ratio of 5:2:1.5 are more conducive to cooperating with the second additive in the process of forming an inorganic film during chemical formation, so that the inorganic matter is uniformly deposited in the organic polymer film, thereby improving the uniformity and density of the SEI film.
[0080] In a preferred embodiment of the present invention, the electrolyte salt includes one or a combination of several of XPF6, XClO4, XBF4, XAsF6, XFSI, XTFSI, XBOB, XODFB, XCF3SO3, XPO2F2 or XOTFB.
[0081] Wherein, X includes any one of Li, Na or K.
[0082] Preferably, in the lithium ion battery, X is Li.
[0083] Preferably, the molar concentration of the electrolyte salt in the battery electrolyte is 0.5 to 3 mol / L, and the mass percentage of the electrolyte salt is 10 to 30% based on the total mass of the electrolyte as 100%.
[0084] Preferably, the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.
[0085] Preferably, the mass ratio of lithium hexafluorophosphate to lithium bis(fluorosulfonyl)imide is 7.5:9.
[0086] In a preferred embodiment of the present invention, the organic solvent includes one or more of carbonates, halogenated carbonates, carboxylates, propionates, fluoroethers, aromatic hydrocarbons or halogenated aromatic hydrocarbons.
[0087] In the present invention, the carbonate comprises one or a combination of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate or ethyl methyl carbonate. The halogen in the halogenated carbonate or halogenated aromatic hydrocarbon is at least one of F, Cl, Br or I.
[0088] Preferably, the halogenated carbonate comprises one or a combination of fluoroethylene carbonate, difluoroethylene carbonate, difluoropropylene carbonate, trifluoroethyl acetate, trifluoroethyl methyl carbonate, trifluoromethylethylene carbonate, 4-trifluoromethylethylene carbonate, chloroethylene carbonate, di(2,2,2-trifluoroethyl) carbonate, methyl trifluoropropionate, 3,3,3-trifluoroethyl acetate, methyl 2-(trifluoromethyl)benzoate, ethyl 4,4,4-trifluorobutyrate or 1,1,1,3,3,3-hexafluoroisopropyl acrylate.
[0089] Preferably, the carboxylic acid ester includes one or a combination of at least two of propyl butyrate, propyl acetate, isopropyl acetate, butyl propionate, isopropyl propionate, ethyl butyrate, methyl propionate, ethyl propionate or propyl propionate.
[0090] Preferably, the propionate ester is at least one of methyl propionate (EM), ethyl propionate (EP), and propyl propionate (PP).
[0091] Preferably, the fluoroether is an ether containing 7 or less carbon atoms in the molecule.
[0092] Preferably, the halogenated aromatic hydrocarbon is one or a combination of at least two of monofluorobenzene, difluorobenzene, 1,3,5-trifluorobenzene, trifluorotoluene, 2-fluorotoluene or 2,4-dichlorotrifluorotoluene.
[0093] Preferably, the organic solvent includes ethylene carbonate, ethyl methyl carbonate and diethyl carbonate.
[0094] Preferably, the mass ratio of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate is 25:70:5.
[0095] Preferably, based on the total mass of the electrolyte being 100%, the mass percentage of the organic solvent is 40% to 85%, preferably 73%.
[0096] Specifically, the method for preparing the battery electrolyte comprises:
[0097] After the organic solvent, the first additive and the second additive are mixed uniformly, the electrolyte salt is added and mixed uniformly again.
[0098] According to a second aspect of the present invention, there is provided a battery comprising the non-aqueous battery electrolyte as described above.
[0099] Preferably, the battery comprises a lithium ion battery, a sodium ion battery, a potassium ion battery or a supercapacitor.
[0100] Preferably, the battery is a lithium-ion battery.
[0101] Preferably, the positive electrode material of the lithium-ion battery includes a nickel-cobalt-manganese-oxide lithium positive electrode material.
[0102] Specifically, the positive electrode of the battery includes a binder PVDF-900, a composite conductive agent Super-P, a nickel cobalt lithium manganese oxide positive electrode material and a solvent NMP (N-methyl-2-pyrrolidone, N-methylpyrrolidone).
[0103] Preferably, the negative electrode material of the lithium-ion battery is graphite, or a composite material of single crystal silicon and graphite, or a composite material of silicon oxide and graphite, or lithium titanate, or Nb2O5.
[0104] Preferably, the negative electrode material of the lithium-ion battery includes a silicon-carbon negative electrode material.
[0105] Specifically, the negative electrode raw materials of the battery include silicon-carbon composite material, conductive agent Super-P, solvent CMC, H2O and binder SBR.
[0106] Example
[0107] The present invention is further described in detail below in conjunction with the embodiments. It is to be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.
[0108] In the following examples, unless otherwise specified, all raw materials are commercially available products.
[0109] According to the electrolyte composition shown in Table 1, the organic solvent, the first additive and the second additive were mixed evenly, and then the electrolyte salt was added and mixed evenly again.
[0110] Then, the electrolyte is added to the battery to prepare a lithium-ion battery, wherein the negative electrode material of the lithium-ion battery is a silicon-carbon composite material, a conductive agent Super-P, a solvent CMC, H2O and a binder SBR, and the positive electrode material of the lithium-ion battery is a binder PVDF-900, a composite conductive agent Super-P, a nickel-cobalt-manganese oxide positive electrode material and a solvent NMP (N-methyl-2-pyrrolidone).
[0111] The positive electrode and the negative electrode are coated, sliced, rolled, divided, dried, taped, wound up, and dried at 80° C. for 48 hours, and then the electrolyte is added to seal the lithium-ion battery, and then left for 24 hours, and then formed, and then the primary final sealing, aging, and secondary final sealing are carried out in sequence to prepare a lithium-ion soft-pack battery.
[0112] The battery was then tested for its cycle performance and high-temperature storage performance.
[0113] The electrolyte compositions of Examples 1-21 and Comparative Example 1 are shown in Table 1.
[0114] Table 1 Electrolyte compositions of Examples 1 to 21 and Comparative Example 1
[0115]
[0116]
[0117]
[0118] Performance Testing
[0119] The electrolytes described in Examples 1-21 and Comparative Example 1 were tested as follows:
[0120] (1) Cycle performance: The high temperature cycle test needs to be carried out in a 45℃ oven, and the battery is clamped and left for 2 hours. The charge and discharge voltage range is 2.75V~4.2V, the charging current is 1C (1.8A) to 4.2V, 4.2V constant voltage charging to a cut-off current ≤0.05C (0.1A), after standing for 5 minutes, 1C (1.8A) discharge to 2.75V, and stand for 5 minutes; the charge and discharge cycle is repeated in this way, and the capacity retention rate of different cycles is calculated.
[0121] (2) High temperature storage performance: Fully charge capacity C1 at 0.2C constant current and constant voltage at room temperature, and measure thickness d1 at the same time. Then stand at 60℃ for 7 days, take out and immediately test hot thickness d2, cool to room temperature and leave for 4 hours to test cold thickness d3. Then discharge capacity at 1C (2.0A) at room temperature is recorded as C2, and the average discharge capacity is calculated by three cycles and recorded as C3. The capacity retention rate is C2 / C1, the capacity recovery rate is C3 / C1, the thermal expansion rate is d2 / d1, and the cold expansion rate is d3 / d1.
[0122] The lithium ion batteries prepared by the electrolyte formulations of Examples 1-21 and Comparative Example 1 were tested for normal temperature, high temperature cycle performance and high temperature storage performance. The test results are shown in Table 2-4:
[0123] Table 2 Room temperature cycle performance of lithium ion batteries prepared in Examples 1 to 16 and Comparative Example 1
[0124]
[0125]
[0126] Table 3 High temperature cycle performance of lithium ion batteries prepared in Examples 1 to 16 and Comparative Example 1
[0127]
[0128]
[0129] Table 4 High temperature storage performance of lithium ion batteries prepared in Examples 1 to 16 and Comparative Example 1
[0130]
[0131] In summary, the use of the second additive can improve the cycle performance and high temperature storage performance of the battery through the synergistic effect between the first additive and the second additive and between the functional groups. From Tables 2 to 4, it can be seen that the performance of the embodiments has a certain degree of improvement over the comparative examples; the addition of such additives in a low or high amount is not conducive to the performance. In particular, for lithium-ion batteries whose negative electrode materials are graphite, a composite material of single crystal silicon and graphite, or a composite material of silicon oxide and graphite, adding an appropriate amount of additives can give them excellent performance.
Claims
1. A non-aqueous battery electrolyte, characterized in that: The electrolyte comprises an electrolyte salt, an organic solvent, a first additive and a second additive; The first additive includes fluoroethylene carbonate, 1,3-propane sultone and vinyl sulfate; The second additive includes one or more of compound A as shown in formula I, compound B as shown in formula II, or compound C as shown in formula III; wherein R1, R4, and R5 are each independently hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, C3-C6 cycloalkyl, substituted or unsubstituted phenyl, nitrogen-containing phenyl substituent, furyl, thienyl, pyrrolyl, or pyridyl; R2 and R3 are each independently a C1-C6 alkyl group.
2. The non-aqueous battery electrolyte according to claim 1, characterized in that The substituents of the C1-C6 alkyl group include halogen, benzene or hydrocarbonoxy, and the hydrocarbonoxy includes alkoxy, alkenyloxy or alkynyloxy; Preferably, the substituents of the C2-C6 alkenyl group include halogen or benzene; Preferably, the substituents of the C2-C6 alkynyl group include halogen or benzene; Preferably, the substituents of the phenyl group include halogen, alkyl or halogen-substituted alkyl; Preferably, the nitrogen-containing benzene substituent includes phenylnitro, phenylamino or benzonitrile.
3. The non-aqueous battery electrolyte according to claim 1, characterized in that R1 is -C(CH3)3, -C6H4C(CH3)3, -CH3 or CH2CHCH2OCH2-; Preferably, R4 is -CH2CH2CH3, -CH2OCH3, CF3, -C6H4CF3, -C6H 11 or -C6H5; Preferably, R5 is -H, -CH2OCH2CCH, -C6H5 or -C5H4N.
4. The non-aqueous battery electrolyte according to claim 1, characterized in that Compound A includes one or more of the following compounds: Preferably, compound B comprises one or more of the following compounds: Preferably, compound C comprises one or more of the following compounds:
5. The non-aqueous battery electrolyte according to claim 1, characterized in that Based on the total mass of the electrolyte being 100%, the mass percentage of the second additive is 0.5 to 4%; Preferably, the mass percentage of the first additive is 3-10%.
6. The non-aqueous battery electrolyte according to claim 1, characterized in that In the first additive, the mass ratio of fluoroethylene carbonate, 1,3-propane sultone and vinyl sulfate is 5:2:1.
5.
7. The non-aqueous battery electrolyte according to claim 1, characterized in that The electrolyte salt includes one or a combination of XPF6, XClO4, XBF4, XAsF6, XFSI, XTFSI, XBOB, XODFB, XCF3SO3, XPO2F2 or XOTFB; wherein X includes any one of Li, Na or K; Preferably, in the lithium ion battery, X is Li; Preferably, the total mass of the electrolyte is 100%, and the mass percentage of the electrolyte salt is 6.25% to 37.5%; Preferably, the lithium salt comprises lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide; Preferably, the mass ratio of lithium hexafluorophosphate to lithium bis(fluorosulfonyl)imide is 7.5:
9.
8. The non-aqueous battery electrolyte according to claim 1, characterized in that The organic solvent includes one or more of carbonate, halogenated carbonate, carboxylate, propionate, fluoroether, aromatic hydrocarbon or halogenated aromatic hydrocarbon; Preferably, the organic solvent comprises ethylene carbonate, ethyl methyl carbonate and diethyl carbonate; Preferably, the mass ratio of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate is 25:70:5; Preferably, based on the total mass of the electrolyte being 100%, the mass percentage of the organic solvent is 40% to 85%, preferably 73%.
9. A battery, characterized in that: The battery comprises the non-aqueous battery electrolyte according to any one of claims 1 to 8.
10. The battery according to claim 9, characterized in that The battery comprises a lithium ion battery, a sodium ion battery, a potassium ion battery or a supercapacitor; Preferably, the battery is a lithium-ion battery; Preferably, the negative electrode material of the lithium-ion battery is graphite, a composite material of single crystal silicon and graphite, or a composite material of silicon oxide and graphite, lithium titanate or Nb2O5.
